2015 ASEE Annual Conference and Exposition Proceedings
DOI: 10.18260/p.23554
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Data Management Plans: Where Librarians Can Make a Difference

Abstract: is the research data services manager at the University of Michigan Library. In this role, he explores the application of the theories, principles, and practices of library science beyond the domain of traditional library work. In particular, Carlson seeks to increase the Library's capabilities and opportunities to provide services supporting data-related research. Much of his work is done through direct collaborations and partnerships with research faculty. Carlson is one of the architects of the Data Curatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…To maintain confidentiality of NSF proposal content, the DMPs were secured on a password-protected, internal library server for the duration of the study. The DMPs were evaluated using a modified version of a rubric previously used by researchers at the University of Michigan (Nicholls et al, 2014;Samuel et al, 2015). Our rubric (Appendix 1) consisted of 15 items addressing the inclusion of information requested by the NSF (National Science Foundation, 2014) and other common pieces of information often found in DMPs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To maintain confidentiality of NSF proposal content, the DMPs were secured on a password-protected, internal library server for the duration of the study. The DMPs were evaluated using a modified version of a rubric previously used by researchers at the University of Michigan (Nicholls et al, 2014;Samuel et al, 2015). Our rubric (Appendix 1) consisted of 15 items addressing the inclusion of information requested by the NSF (National Science Foundation, 2014) and other common pieces of information often found in DMPs.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the Data Management Plans as a Research Tool (DART) project, led by Rolando et al (2015), developed and tested an evaluation rubric for NSF DMPs to create a robust and standardized assessment tool for DMPs to enable cross-institutional comparisons. An early version of the DART rubric was used by Samuel et al (2015) to assess 29 DMPs from Engineering faculty at the University of Michigan. They found that the overall quality of DMPs varied greatly and identified elements that were often missing from DMPs, including clear roles and responsibilities for data management, metadata standards for describing research data, and policies for protecting intellectual property rights.…”
Section: Literature Review: Content Analysis Of Dmpsmentioning
confidence: 99%
“…A number of instructional and training programs for engineering faculty and researchers have been developed and implemented (Carlson et al, 2011;Johnston and Jeffrys, 2014). Many of these programs are built around data management plan assistance (Samuels at al, 2015;Wang and Fong, 2015;Nelson, 2015). Zilinski et al (2014) have developed a program directed at undergraduate STEM students.…”
Section: Instructional Programmentioning
confidence: 99%
“…In response to federal grant agency and publisher mandates for data sharing, science and technology libraries have become actively involved in designing and implementing programs to meet the data management needs of researchers (Tenopir et al, 2015;Samuels et al, 2015). Along with these new opportunities comes challenges in establishing effective programs and services that support the data workflow needs of researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Samuel and others analyzed twenty-nine data management plans (DMP), specifically related to National Science Foundation grant proposals, to understand better, how faculty approach data management. The results help librarians build a foundation for future DMP services [2]. Coates and others examined five case studies that highlight common challenges for librarians to evaluate existing research data services in academic libraries, and suggested that evidence-based approach provides valuable information for assessing the still-emerging services [3].…”
Section: Selected Literature Reviewmentioning
confidence: 99%